Conservation, human values and democracy. (January 2014) - Rull, Valentí
<x xml:space="preserve">Abstract</x> Humans are aware of the precarious state of the environment, but we show little inclination to address the problem. Because we fail to grasp our role as individuals in Nature, strategies for a more sustainable future can only come from advances in awareness we make as societies.<boxed-text content-type="graphic" id="embr201337942-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>